Evaluation of Peripheral Immune Activation in Amyotrophic Lateral Sclerosis - Wang, Mengli; Liu, Zhen; Du, Juan; Yuan, Yanchun; Jiao, Bin; Zhang, Xuewei; Hou, Xuan; Shen, Lu; Guo, Jifeng; Jiang, Hong; Xia, Kun; Tang, Jianguang; et al. (Frontiers in Neurology, 2021)
Accumulating evidence has revealed that immunity plays an important role in amyotrophic lateral sclerosis (ALS) progression. However, the results regarding the serum levels of immunoglobulin and complement are inconsistent in patients with ALS. Although immune dysfunctions have also been reported in patients with other neurodegenerative diseases, few studies have explored whether immune dysfunction in ALS is similar to that in other neurodegenerative diseases. Therefore, we performed this study to address these gaps. In the present study, serum levels of immunoglobulin and complement were measured in 245 patients with ALS, 65 patients with multiple system atrophy (MSA), 60 patients with Parkinson’s disease (PD), and 82 healthy controls (HCs). The pooled results showed that patients with ALS had higher C4 levels than HCs. Multiple comparisons revealed that no significant differences existed between patients with ALS and other neurodegenerative diseases in immunoglobulin and complement levels. In addition, we found that the IgG levels were lower in early-onset ALS patients than in late-onset ALS patients and HCs, and the correlations between age at onset of ALS and IgG or IgA levels were significant positive. In conclusion, our data supplement existing literature on understanding the role of peripheral immunity in ALS.